(3GdOjGQGJs - (3Ydj Hf eMeO GdTGHTJj, CHh GdMSf,J (B388 (3g` s ((3YHO GdMdje Hf eMeO Hf YHO GdhgGH GdOeTbi s)
(3ChdgG (B:s
(3Chd eG ajg (B: (3OjQOQeGdS s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B325 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B202s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B2 - (3U (B64 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs